2014
DOI: 10.1039/c4cc06207h
|View full text |Cite
|
Sign up to set email alerts
|

High-performance CO2-philic graphene oxide membranes under wet-conditions

Abstract: Ultrathin graphene oxide (GO) (<5 nm) membranes were prepared by spin-casting onto microporous polymeric support membranes. GO membranes exhibited a highly CO2 permeable character, which is suitable for CO2 separation. In the presence of water vapour, high CO2 selectivity (e.g., CO2/H2, CO2/N2, and CO2/CH4) was achieved by enhanced CO2 sorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 38 publications
(40 reference statements)
5
63
0
Order By: Relevance
“…[ 11,12 ] Up to now, many breakthroughs about GO membranes have been discovered and reported. [ 13 -16 ] The exciting selective permeation results, including our recent studies, [ 17,18 ] have demonstrated that GO is a new-generation material platform for high-performance separation membranes with inspiring fast water, [ 18 -21 ] gas, [ 14,15,17,22 ] and ion [ 23,24 ] transport channels. These intrinsic and unique channels offer a wide variety of applications for small-molecule separation under aqueous conditions [ 16,18 -21,23,24 ] or for the separation of…”
Section: Introductionmentioning
confidence: 98%
“…[ 11,12 ] Up to now, many breakthroughs about GO membranes have been discovered and reported. [ 13 -16 ] The exciting selective permeation results, including our recent studies, [ 17,18 ] have demonstrated that GO is a new-generation material platform for high-performance separation membranes with inspiring fast water, [ 18 -21 ] gas, [ 14,15,17,22 ] and ion [ 23,24 ] transport channels. These intrinsic and unique channels offer a wide variety of applications for small-molecule separation under aqueous conditions [ 16,18 -21,23,24 ] or for the separation of…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, gas transport mechanisms in these two membranes are still unclear and confusing. It should be noted that the performances of both membranes could be improved with the aid of water, and the similar phenomenon was also observed in other graphene oxide membranes [97]. However, the role of water was not intensively studied.…”
Section: Carbon-based Membranesmentioning
confidence: 72%
“…The reason for this interesting phenomenon is still unclear, and it might be related to the interaction mechanism between TSILs and CO 2 . However, these TSILs in supported liquid membranes could still possibly be lost at a sufficient pressure difference due to the lack of strong interactions with 97 supports.…”
Section: Facilitated Transport Membranesmentioning
confidence: 97%
“…Despite the huge scientific and technological interest focused on graphene, only few reports so far consider in sufficient detail the outstanding gas permeability and selectivity properties of ultrathin (< 20 nm) graphene oxide (denoted hereafter as GO) membranes, consisting of few-layered supported GO sheets [1][2][3][4][5][6]. Moreover, even if self-supported GO films have already been prepared and evaluated against a variety of potential applications, ranging from their use as membranes for desalination [5] and scaffolds for bone regeneration [7] up to their involvement in the development of high performance supercapacitors [8], this is the first time that self-supported GO membranes (instead of supported membranes) are prepared and evaluated for gas and vapor separation related applications.…”
Section: Introductionmentioning
confidence: 99%